2016
DOI: 10.11113/jt.v78.9939
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF SOLID STATE FERMENTATION BY Monascus purpureus ON PHENOLIC CONTENT AND BIOLOGICAL ACTIVITIES OF COCONUT TESTA AND RICE BRAN

Abstract: Solid-state fermentation (SSF) is an alternative low cost useful process that has many important applications in the field of biotechnology.  In this study, SSF has been employed as a process for the production of value-added agricultural by-product using coconut testa (CT), rice bran (RB) and the combination of both substrates (CT-RB). The effect of SSF by Monascus purpureus on total phenolic content (TPC), antioxidant, anti-tyrosinase and anti-elastase of the substrates were studied and compared with its non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Preliminary tests identified that water content <12 per cent in the CB decreased fermentation or prevented production of the pigments, and because of this, the ratio 1:1 of water (mL): substrate (g) was used in SSF. The time (4, 8, 12 and 16 days) (Dikshit and Tallapragada, 2011), temperature (16, 24 and 32°C) (Dikshit and Tallapragada, 2011; Jamaluddin et al , 2016; Sehrawat et al , 2017), and amount of spores (10 5 , 10 6 and 10 7 spores for mL) (Srianta et al , 2016; Bei et al , 2018) used in this fermentative process were chosen based on reports from the literature in other subtracts. One SSF treatment was considered for new ingredient with red color production.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary tests identified that water content <12 per cent in the CB decreased fermentation or prevented production of the pigments, and because of this, the ratio 1:1 of water (mL): substrate (g) was used in SSF. The time (4, 8, 12 and 16 days) (Dikshit and Tallapragada, 2011), temperature (16, 24 and 32°C) (Dikshit and Tallapragada, 2011; Jamaluddin et al , 2016; Sehrawat et al , 2017), and amount of spores (10 5 , 10 6 and 10 7 spores for mL) (Srianta et al , 2016; Bei et al , 2018) used in this fermentative process were chosen based on reports from the literature in other subtracts. One SSF treatment was considered for new ingredient with red color production.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been conducted to determine the effects of fermentation on the nutritional content, antioxidant activity and bioactive compounds in rice bran. The fermentation process is carried out using molds, such as Monascus pilosus 11) , Monascus purpureus 22,23) , Rhizopus oryzae 19,24,25) , Aspergillus oryzae 25) , Rhizopus oligosporus 20, 23, 26−28) , lactic acid bacteria (Pediococcus acidilactici, Lactococcus lactis and Pediococcus pentoseous) 29) and mushrooms (Pleurotus sapidus) 30) .…”
Section: Fermentation Can Increase the Active Compounds Of Rice Branmentioning
confidence: 99%
“…From the economic and environmental point of views, with the large availability and the composition that always rich in bioactive compounds, reutilization of these wastes for the production of beneficial products would be effective in terms of cost and environmental pollution [27]. Few studies have revealed that plant by-products such as coconut testa, rice bran, and cocoa pod also exhibited anti-elastase activities with percentage of inhibitions of 6.80±3.16%, 9.16±0.54%, and 2.54±0.04%, respectively [28,29]. These findings clearly emphasize that red pitaya peels possessed a much higher elastase inhibition properties which can be utilized as an efficient anti-aging agent in the formulation of plant-based cosmetic and pharmaceutical products.…”
Section: Anti-elastase Activitymentioning
confidence: 99%